Knowledge, attitude, and practice towards breast cancer and breast cancer screening among women in Homa Bay County, Kenya - Odhiambo, Felix Blair; Oyore , John Paul; Agina, Bom (International Journal Of Community Medicine And Public Health, 2023)
Background: Late diagnosis of breast cancer lowers survival rates in resource-poor nations like Kenya. Due to a lack of screening programs, breast cancer awareness, and modern cancer treatment treatments. Rural areas, where most poor people live, are worse. The study examined breast cancer knowledge, attitude, and practice among Homa Bay County women. Methods: A cross-sectional study included 340 samples from two sub counties chosen for their rural nature. 170 women were randomly selected from from each sub county. Questionnaires collected data. Four significant informants were interviewed. Only descriptive statistics were used in data analysis. Results: The results showed lower level of breast cancer screening of 9.7%. Average knowledge was 44.39%. The average score in attitude was 1.7 showing a positive attitude towards breast cancer. The mean age of the participants was 44.30±14.32 in Ndhiwa and 45.16±14.35 in Kasipul. The general knowledge for breast cancer screening was considerably poor. Majority scored below 60% was considered low. In in terms of attitude, women had a positive attitude towards breast cancer screening and thought these was contradicted by key informant who said most had negative attitude. In terms of practice toward breast cancer screening services, only a paltry 9.7 % had gone for screening. Conclusions: Clinical breast examination was preferred over mammography. This study will educate Kenyan public health implementers on ways to improve screening for rural women. Education on early screening towards breast cancer can help in improving breast cancer screening uptake. Breast cancer awareness was considerably lower. Health policymakers can use this findings to improve on cancer management.